The Teaching Value Workshop - Christopher Moriates; Neel Shah; Andrew Levy; Michelle Lin; Robert Fogerty; Vineet Arora (Association of American Medical Colleges, 2014)
Abstract Introduction Medical educators have recently been charged with teaching clinicians about healthcare costs and value. The ACGME currently requires under their systems-based practice competency that resident physicians maintain cost awareness while practicing medicine, and some have suggested that this be elevated to an additional general competency. Despite these recent efforts, most medical training programs currently lack curricula aimed at healthcare value, and trainees demonstrate significant gaps in their knowledge related to medical costs. This resource is designed to allow medical educators to engage medical students, resident physicians, faculty clinicians, and/or other educators in innovative efforts to teach about healthcare value. Methods Our workshop includes a PowerPoint presentation that features video presentations from some of our competition finalists sharing real stories of success from clinicians that created their own high-value care (HVC) programs. The resources also include our novel culture, oversight, systems, training (COST) framework for evaluating programs and designing interventions, and a handout template for exploring possible projects at participants' own institutions. An evaluation form to provide iterative feedback for the workshop is also provided. Results This workshop was first delivered at the 2013 AAMC Annual Meeting. Based on the feedback form 90% of participants reported they would recommend the workshop to a colleague; 74% planned on making a change based on their experience with the workshop; 45% planned to develop or implement a HVC project at their home institution; 62% planned to initiate conversations with trainees about HVC; and 71% planned to initiate conversations with faculty about HVC. Nearly all of our participants (98%) thought that hearing from some of the competition finalists was inspiring. Seventy-six percent thought the "COST" framework was helpful. At the end of our session, 73% of participants felt more confident addressing cost of care issues, and 70% felt more confident teaching about cost-conscious care. Discussion Most medical training programs currently lack curricula aimed at healthcare value, and trainees demonstrate significant gaps in their knowledge related to medical costs. This resource successfully introduces a framework for the design and evaluation of emerging HVC curricula, and provides inspiration for different approaches to operationalize projects and tools for participants to design their own programs within their institutions.